Death anxiety and cyberchondria in patients with chronic obstructive pulmonary disease: A cross-sectional study (Colombia Medica, 2025)
IntroductionIt is suggested that chronic obstructive pulmonary disease (COPD) patients have high death anxiety and the majority of them tend to search for COPD-related information on the internet.ObjectiveExplore the association between death anxiety and cyberchondria in patients with COPDMethodsThis descriptive, cross-sectional study included 143 patients diagnosed with COPD aged 45 years or older, who had no sensory impairments affecting communication, were cognitively intact, and actively used the internetResultsA multiple regression analysis examining the Cyberchondria Scale (CS-12) total score in relation to sociodemographic and clinical characteristics found that marital status, regular use of medications, having a COPD exacerbation in the last 6 months, and daily internet use time together explained 35.8% of the variance in the Cyberchondria Scale (CS) score (Adj R2=  0.358, p